Correction to: A case of misalignment: the perspectives of local and national decision-makers on the implementation of psychological treatment by telephone in the Improving Access to Psychological Therapies Service - Kelly Rushton (BMC Health Services Research, 2020)
In the original publication of this article [1], the article title should be revised as blow.